Mutação genética comprovada associada ao aumento do gradiente na via de saída do ventrículo esquerdo ao estresse físico na cardiomiopatia hipertrófica - Melo, Bráulio Cruz (2022)
Background: Hypertrophic cardiomyopathy (HCM) is a disease defined by the presence of left ventricular hypertrophy, often causing an obstruction in the Left Ventricular Outflow (LVOT). The delineation of the severity of the obstruction has several clinical implications, including the therapeutic decision. The echocardiogram is the initial test of choice for diagnostic investigation, and the physical stress echocardiogram (PE) complements it by quantifying the LVOT gradient. As it is a genetically inherited disease, genetic research will serve as a guide and possible investigation of family members. Objective: To evaluate the LVOT gradient at rest and on exertion during PE and relate it to the genetic data of a population with a previous echocardiographic diagnosis of HCM. Methods: In this research, data were analyzed at rest and exertion during PE, including the LVOT gradient, in the diagnosis of HCM with or without gradient, in order to investigate which are the most relevant diagnostic markers in HCM through PE. DNA was obtained and analyzed through blood or saliva samples, and the sequencing of genes related to HCM was performed on the DNA obtained in each sample. Results: Eighty patients were studied, with 61% male. Beta-blockers were the most used medication (47%). Palpitation was the most common symptom (62%), followed by chest pain (50%), dyspnea (40%) and syncope (22%). In the genetic test, 42,8% had a pathogenic variant for HCM. Of these, more than 40% were in the sarcomeric genes MYH7 and MYBPC3. There were 71 patients who underwent resting echocardiography (89% of the sample). The mean septum was 15.5mm. In those patients with a pathogenic variant in a sarcomeric gene, the mean septum was 16.4. 90% had some sign of diastolic dysfunction. Twenty-four PE tests were performed, 14 of which were performed on the treadmill and 10 on the bicycle. 48% presented a significant increase in gradient in the effort phase (labile gradient). Regarding arrhythmias, Ventricular ectopias were a little more frequent in the bicycle method (33%, against 28% in the treadmill method), and occurred in those patients who came closer to the maximum HR (around 90% of the HR maximum for age). Conclusions: The performance of PE in HCM showed that many patients may have a labile gradient in the LVOT, and many have arrhythmia at peak exertion, especially in those with a pathogenic variant for HCM. Major changes in the clinical profile and treatment depend on a refined risk stratification after the initial diagnosis, including patient education and the need for genetic investigation of family members.